Perbandingan Kecepatan Perahu 1 GT Menggunakan Propeller Dua Daun dan Tiga Daun Pada System Water Jet - Ikhsan, Muhammad; B, Siswandi; Jupri; Efrizal; Muhammad Ryan Saputra; Bima Kurniawan (Jurnal Serambi Engineering, 2026)
Indonesia, as an archipelagic country with extensive marine areas, relies on small vessels as the main means of transportation for coastal communities; therefore, an efficient, safe, and suitable propulsion system for shallow waters is required. This study aims to analyze the effect of the number of propeller blades on the speed of a 1 GT boat equipped with a water jet propulsion system. An experimental method was applied by conducting speed tests in shallow waters using a 4-inch diameter water jet and a 7 HP Rubin engine. The tests were carried out using two-blade and three-blade propellers, each tested four times on the same boat, engine, and location. Primary data were obtained from direct testing and speed measurements, while secondary data included engine specifications, 1 GT boat characteristics, and water jet design data. The analysis was conducted using descriptive and comparative methods. The results show that the three-blade propeller produced a higher average speed of 4.88 knots compared to 4.13 knots for the two-blade propeller. The maximum speed achieved by the three-blade propeller was 5.3 knots, while the two-blade propeller reached 4.4 knots. These results indicate that the three-blade propeller generates greater thrust, making it more effective for improving the speed of small boats using water jet systems in shallow waters.